SEASON OF BIRTH IN OBSESSIVE‐COMPULSIVE DISORDER. Issue 12 (9th October 2013) - Cheng, Chin; Lin, Ching‐Heng; Chou, Po‐Han; Tsai, Chia‐Jui; Lan, Tsuo‐Hung; Nestadt, Gerald
<x xml:space="preserve">Abstract</x> Background Effects of season of birth (SOB) have been documented in numerous neuropsychiatric disorders. To date, few studies have evaluated this issue in obsessive‐compulsive disorder (OCD). The aim of this study was to investigate the birth seasonality in OCD. Methods This study was based on Taiwan National Health Insurance Research Database. Data for the birth‐year period 1956–1991 were extracted for analysis (273, 837 males and 292, 207 females). The International Classification of Diseases, 9th Revision, Clinical Modification (ICD‐9‐CM), code 300.3 was used as the diagnosis of OCD. Birth seasonality was compared between the OCD patients (519 males and 528 females) and the general population. Results The birth distributions across the 12 months were significantly different between the OCD patients and the general population (P‐value for the Walter & Elwood's test = .04). A significant decrease of births from March to July and an excess from August to November in OCD patients as compared to the general population was noted (the relative risk of these months vs. the rest months of the year: 0.85 (95% CI 0.74–0.96) and 1.19 (95% CI 1.05–1.36). Effects of SOB in OCD were present in males (P‐value for the Walter & Elwood's test = .03) but not in females. Conclusion The findings support an effect of SOB in people with OCD, especially for men.